Kinetics and Mechanism of Oxidation of o-Toluidine by Sodium-N-Chlorobenzene Sulphomide (Chloromine-B) in Acid Medium - Raman, M.G. (Asian Journal of Chemistry, 2010)
The kinetics of the oxidation of o-toluidine by chloramines-B [CAB] has been studied in aqueous sulfuric acid at 303 K. The rate shows first order dependence on [CAB], fractional order in [o-toluidine] and inverse order in [H+]. The variation of ionic strength, change in dielectric constant of the medium, addition of the reaction product (benzene sulphonamide) and halide ions had no significant effect on the reaction rate. The oxidation product has been identified as o,o´ -dimethylazobenzene. Thermodynamic parameters were evaluated. The protonation constant of monochloramine- B has been evaluated to be 64.5 ± 3.